Real price of health-experiences of out-of-pocket costs in Australia: protocol for a systematic review - Anne Parkinson; Danielle Butler; Jane Desborough; Vanessa Fanning; Shelley Ting-Li Wang; Hsei Di Law (BMJ Open)
Introduction Australians have substantial out-of-pocket (OOP) health costs compared with other developed nations, even with universal health insurance coverage. This can significantly affect access to care and subsequent well-being, especially for priority populations including those on lower incomes or with multimorbidity and chronic illness. While it is known that high OOP healthcare costs may contribute to poorer health outcomes, it is not clear exactly how these expenses are experienced by people with chronic illnesses. Understanding this may provide critical insights into the burden of OOP costs among this population group and may highlight policy gaps.Method and analysis A systematic review of qualitative studies will be conducted using Pubmed, CINAHL Complete (EBSCO), Cochrane Library, PsycINFO (Ovid) and EconLit from date of inception to June 2022. Primary outcomes will include people’s experiences of OOP costs such as their preferences, priorities, trade-offs and other decision-making considerations. Study selection will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and methodological appraisal of included studies will be assessed using the Critical Appraisal Skills Programme. A narrative synthesis will be conducted for all included studies.Ethics and dissemination Ethics approval was not required given this is a systematic review that does not include human recruitment or participation. The study’s findings will be disseminated through conferences and symposia and shared with consumers, policymakers and service providers, and published in a peer-reviewed journal.PROSPERO registration number CRD42022337538.